THE EFFECT OF DRIBBLING EXERCISES WITH TOOLS AND DRIBBLING WITH OPPONENT AND THE EYE-FOOT COORDINATION ON INCREASING THE DRIBBLING SKILL OF EXTRCURRICULAR PARTICIPANTS - Afif Rafiun; Muhammad Yamin (STKIP HARAPAN BIMA, 2022)
The purpose of this research was to know: (1) the effect between Dribbling Exercises with tools and Dribbling with an opponent on increasing the dribbling skill of extracurricular participants. (2) the effect between the eye-foot coordination (high eye-foot coordination and low eye-foot coordination) on increasing the dribbling skill of extracurricular participants. (3) the interaction between Dribbling Exercises with tools and Dribbling Exercises with the opponent and the eye-foot coordination (high and low) on increasing the dribbling skill of football extracurricular participants of Bima regency. This research used an experimental method with a 2x2 factorial design. The result of data analysis showed that (1) there was a significantly different effect between dribbling exercises with tools and dribbling exercises with an opponent on increasing the dribbling skill of football extracurricular participants, which was proved from P= 0.000 ≤ 0.05. it was indicated that dribbling exercises with tools are better than dribbling exercises with an opponent. (2) there was a significantly different effect between high eye-foot coordination exercise and low eye-foot coordination exercise on increasing the dribbling skill of extracurricular participants, which was proved from P= 0.001 ≤ 0.05. it was indicated that high eye-foot coordination exercise was better than low eye-foot coordination exercise. (3) there was no significant interaction between dribbling exercise with (tooling and opponents) and eye-foot coordination exercise (high and low), it was proved from P= 0.000 ≤ 0.05.